2020
DOI: 10.1016/j.csl.2019.101024
|View full text |Cite
|
Sign up to set email alerts
|

Voice biometrics security: Extrapolating false alarm rate via hierarchical Bayesian modeling of speaker verification scores

Abstract: How secure automatic speaker verification (ASV) technology is? More concretely, given a specific target speaker, how likely is it to find another person who gets falsely accepted as that target? This question may be addressed empirically by studying naturally confusable pairs of speakers within a large enough corpus. To this end, one might expect to find at least some speaker pairs that are indistinguishable from each other in terms of ASV. To a certain extent, such aim is mirrored in the standardized ASV eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Next, use the generated sets of scores to estimate P N FA (τ ) using ( 4). We used this approach in [3] where a location-scale model with Gaussian base distribution was trained to maximize model log-likelihood [17]. Different from [3], the models proposed in this work are instances of implicit generative models: they are specified through a forward stochastic procedure for data generation, but do not allow direct likelihood evaluation [23,24].…”
Section: Training Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, use the generated sets of scores to estimate P N FA (τ ) using ( 4). We used this approach in [3] where a location-scale model with Gaussian base distribution was trained to maximize model log-likelihood [17]. Different from [3], the models proposed in this work are instances of implicit generative models: they are specified through a forward stochastic procedure for data generation, but do not allow direct likelihood evaluation [23,24].…”
Section: Training Methodsmentioning
confidence: 99%
“…The first set was used to train the ASV systems. The second one is the standard Voxceleb1 evaluation protocol [32], used as a sanity check of our ASV systems (see [3] for details). The third set which contains 1000 male and 1000 female speakers was used to compute scores for training models for P N FA extrapolation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voice has also been investigated with voice mimicry attack (Vestman et al 2020) and found to be vulnerable. Voice biometric security is normally tested against general datasets with less percentage of similar signature imposter data (Shirvanian et al 2019;Sholokhov et al 2020). The testing of ASV systems needs to incorporate the closest imposter model framework for more accurate results (Lakshmi et al 2020) with the use of chaotic maps.…”
Section: Voice Biometric Recognitionmentioning
confidence: 99%
“…As one of the most urgent problems in this fi eld, we can mention the necessity of regular updating of accumulated BPD samples [6,7]. It seems to be especially important in connection with recording of voice samples [8][9][10]. Due to the phenomenon of variability of speech signal on the sound (phonetic) level of its perception, any voice samples inevitably ages with time and gradually loses its consumer quality [11,12].…”
mentioning
confidence: 99%